2022
DOI: 10.3390/rs14174303
|View full text |Cite
|
Sign up to set email alerts
|

Global Empirical Models for Tropopause Height Determination

Abstract: The calculation of the tropopause height is crucial to the investigation of fundamental interactions between the troposphere and stratosphere, playing an essential role in areas such as climatology, geodesy, geophysics, ecology, and aeronautics. Since the troposphere and stratosphere have many distinct features, it is possible to define the boundary between them using different variables, such as temperature lapse rate, potential vorticity and chemical concentrations. However, according to the chosen variable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…In the northern hemisphere, the dynamical tropopause is de ned by PV values in the range of 1-4 PVU (1 (Kunz et al 2011). A de nition of the blended tropopause combines the characteristics of both dynamical and thermal tropopause (Wilcox et al 2012;Mateus et al 2022). In this paper, the dynamical tropopause is de ned as the lower height of the isosurface of PV at 2 PVU and isentropic surface at θ = 380 K (Hoskins et al 1985;Holton et al 1995 shown in Fig.…”
Section: De Nition Of the Tropopausementioning
confidence: 99%
“…In the northern hemisphere, the dynamical tropopause is de ned by PV values in the range of 1-4 PVU (1 (Kunz et al 2011). A de nition of the blended tropopause combines the characteristics of both dynamical and thermal tropopause (Wilcox et al 2012;Mateus et al 2022). In this paper, the dynamical tropopause is de ned as the lower height of the isosurface of PV at 2 PVU and isentropic surface at θ = 380 K (Hoskins et al 1985;Holton et al 1995 shown in Fig.…”
Section: De Nition Of the Tropopausementioning
confidence: 99%
“…Additionally, the tropopause serves as the upper limit for the integration of tropospheric parameters in physics and chemistry, including tropospheric temperature [11] and tropospheric column ozone [12]. The TPH can be determined from the use of radiosonde data [7,[13][14][15] or from Global Navigation Satellite System (GNSS) radio occultation (RO) data from different satellites [5,[16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…be determined from the use of radiosonde data [7,[13][14][15] or from Global Navigation Satellite System (GNSS) radio occultation (RO) data from different satellites [5,[16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%